Ontologi Pendidikan Qur’ani dalam Kurikulum SD Plus Tahfizhul Qur’an Annida Salatiga - Mujiburrahman, Mujiburrahman; Ummah, Kholifatul (TSAQOFAH, 2026)
The Kurikulum Pendidikan Qur’ani (Qur’anic Education Curriculum) is an Islamic education framework that positions the Al-Qur’an as the primary source for formulating educational objectives, content, and learning processes, such that it is oriented not only towards knowledge acquisition but also towards the balanced formation of students’ character and spirituality across intellectual, spiritual, moral, and social dimensions. However, systematic studies on the concept of the Kurikulum Pendidikan Qur’ani and its relevance for the implementation of Islamic education in modern educational contexts remain limited. This article aims to examine the concept of the Kurikulum Pendidikan Qur’ani and its relevance to contemporary Islamic educational practice. The study employed a literature review method with a qualitative approach by analysing various works related to Islamic education and Qur’anic values. The findings show that the Kurikulum Pendidikan Qur’ani emphasises the integration of mastery of scientific knowledge and the internalisation of Qur’anic values in students’ lives by positioning the Al-Qur’an as both a normative and pedagogical foundation. These findings affirm that the Kurikulum Pendidikan Qur’ani is relevant for addressing the challenges of modern education, particularly in character formation and the strengthening of students’ spirituality within a holistic Islamic education framework.